Brazil : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Brazil. (IMF Staff Country Reports; Country Report, 2016)
The economy is still in its deepest recession in decades, partly the result of the failure of past policies. The recession has been aggravated by a political crisis, which had, until recently, paralyzed policymaking and further damaged confidence. President Rousseff was impeached for responsibility crimes related to fiscal practices on August 31, and the government that took office in May will remain in charge until January 1st, 2019. Markets have responded positively to the new government's reform agenda, bolstering asset prices and confidence and helping the country ride a positive wave of sentiment toward emerging economies. However, while some high-frequency indicators suggest the recession may be nearing its end, the implementation of much-needed reforms to durably restore policy credibility is subject to risks.